ABSTRACT MODEL POWER FIELD ELECTROMAGNETIC TYPE BUILDING. PART 2 - Igor Pavlovich Popov (Наука. Инновации. Технологии, 2022)
It is shown that in the classical model of the electromagnetic field the direction of the vector field strength does not coincide with the direction of the force acting on an element of the conductor with current induction depends on the properties of the medium, and the tension -no, the divergence of the field is zero, the Ampere law is considered to be a formula in the general case is incompatible with its main result, the law of electromagnetic induction is phenomenological. A model of the formal analogy of the electromagnetic field, which has no specified features, in particular, the formal analogy of the law of electromagnetic induction is a simple consequence of the other properties and relations of the field, while the constructed model satisfies the basic requirement Ampère - unconditional implementation of Newton's third law.